Evaluasi Program Projek Penguatan Profil Pancasila (P5) dalam Kurikulum Merdeka Belajar sebagai Upaya Peningkatan Karakter Siswa Sekolah Dasar di Kecamatan Pariangan - Brilyan, Shabra; Rayendra, Rayendra; Syafril, Syafril; Masnur, Alkadri (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to evaluate the implementation of the Projek Penguatan Profil Pelajar Pancasila (P5) in Kurikulum Merdeka at elementary schools in the Pariangan District. The approach used is a mixed method with a sequential exploratory design, as well as a CIPP (Context, Input, Process, Product) evaluation model. Qualitative data was collected through interviews, observations, and documentation, while quantitative data was obtained through student questionnaires. The instruments used include interview guidelines, observation sheets, and questionnaires. The results of the context evaluation show that schools understand the importance of character education, but still face obstacles in teacher collaboration and resource readiness. The evaluation of the input revealed the limitations of learning resources, infrastructure, teacher competence, and variations in the quality of the teaching modules. The process evaluation shows that project-based learning is beginning to be implemented, but it is not optimal due to a lack of understanding of the P5 concept. Product evaluation shows that assessment and reporting of learning outcomes have not been maximized due to the limitations of teaching tools and teacher assistance. The implementation of P5 shows a positive direction, but there is still a need for improved coordination, continuous training, strengthening resources, and collaboration with parents and the community to shape the character of students